Effects of hypoxia on interval moderate exercise - Adamos, T.; Papanikolaou, Z.; Voutselas, V.; Soulas, D. (Biology of Exercise, 2008)
There is a controversy in the published scientific data whether extended training at altitude increases performance at sea level. The effect of hypoxia at rest and on the response to interval moderate exercise was determined in six healthy male individuals during an incremental 3 × 5min exercise cycle test (5 min recovery) at sea level and in a hypobaric chamber (10000 feet/3100 m altitude). Ventilation rate (VE), breathing frequency (BF), heart rate (HR), cardiac output (Q), blood lactate (Labl) and % of arterial oxygen saturation (SaO2) were measured. Blood samples were drawn at rest and at the end of each exercise bout. Hypoxia led to a significant increase in VE during exercise (81.7 vs. 62, 87 vs. 66, 89 vs. 64 ml/l, for the three exercise bouts, respectively p .05). There was also a significant increase in BF (11.3 vs. 10, 29 vs. 25, 32 vs. 24, 33 vs. 25, p .05), HR (73 vs. 62, 153 vs. 138, 161 vs. 138, 166 vs. 137 b/min, p .05), Q (4.8 vs. 4, 13.1 vs. 12.5, 14.6 vs. 12.2, 15.5 vs. 12.8 l/min, p .05) and Labl (0.41 vs. 0.35, 3.8 vs. 2.6, 4.7 vs 3, 5.9 vs 2.9 mmol/l, p .05) at rest and during exercise. Hypoxia lowered SaO2 at rest and exercise (99.3 vs 98.6, 98.1 vs 95.1, 98.5 vs 95.3, 98.3 vs 95.5%, p .05). The results suggest that there is a hypoxic augmentation of the cardiorespiratory variables measured. Also we concluded that exercise potentiated the acute ventilatory response to hypoxia by increasing VE, breathing frequency, heart rate, cardiac output, blood lactate and decreasing SaO2.